Taxonomic revision of the Lycocerus hanatanii species group (Coleoptera, Cantharidae), with the description of new species from Taiwan - Hsiao, Yun; Okushima, Yûichi; Yang, Ping-Shih; Ko, Chiun-Cheng (European Journal of Taxonomy, 2016)
The Lycocerus hanatanii species group is revised, with the addition of seven taxa: L. araticollis (Fairmaire, 1897), L. nigripennis (Pic, 1938), L. griseopubens (Pic, 1928), L. aurantiacus sp. nov., L. evangelium sp. nov., L. kintaroi sp. nov., and L. yitingi sp. nov. Supplementary descriptions of the males of L. araticollis and L. griseopubens are provided. Lycocerus nigripennis (Pic, 1938) and L. pictus (Wittmer, 1983) are redescribed in detail. Each species is provided with photos or illustrations of genitalia of both sexes and abdominal ventrite VII of the female if available. Distribution maps and a key to the species of the L. hanatanii species group are presented. In addition, the monophyly of the L. hanatanii species group is supported based on a morphological phylogenetic analysis.